ENVIRONMENTAL PROTECTION AND INTERNATIONAL LAW: पर्यावरण संरक्षण व अन्र्तराष्ट्रीय कानून - Malaviya Shodharti, Badrilal (International Journal of Research -GRANTHAALAYAH, 2015)
In order to increase the maximum of its amenities, it is subject to the materialistic earth that the taunting of the environment is decreasing in the speed at which the indiscriminate exploitation of natural resources is being done. The natural environment, the giver of life-giving elements, has reached a critical stage today due to excessive sedation, unlimited quantities of dirty and excreted substances. This has caused a crisis not only on human things but on the whole earth. Therefore, preserving the environment and controlling pollution has become a widespread responsibility of the country. भोतिकवादी पृवत्ति के वशीभूत हो इसांन अपनी सुख सुविधाओं में अधिकाधिक वृद्वि करने के उददेश्य से प्राकृतिक संपदाओ का अविवेक पूर्ण दोहन जिस गति से कर रहा है, उसमें पर्यावरण का ताना बाना चरमरा रहा है । जीवन दायी तत्वों का दाता प्राकृतिक पर्यावरण आज अत्यधिक देाहन, असीमित मात्रा में निकलते गंदे और उत्सर्जित पदार्थो के कारण संकटमय स्थिति में पहुंच गया है । इससे न सिर्फ मानव वस्तु अपितु संपूर्ण पृथ्वी पर संकट छाया हुआ है । इसलिये पर्यावरण को संरक्षित करना एवं प्रदुषण को नियंत्रित करना देश की एक व्यापक जिम्मेदारी बन गई है।